Dentist’s child view and psychological approach (Research, Society and Development, 2021)
In the routine care of the child, professional can come across situations in which the child shows aversive, and avoiding personal contact, especially in cases of first appointment. This study aims to analyze the children's perception about dental surgeon through drawings analysis and verbal characterization. The sample consisted of 108 children aged between 5-11 years of both genders, 59 were patients of pediatric dentistry clinic of west Sao Paulo Presidente Prudente, and 49 students of the school of Tertuliano de Area Leão located in the city of Santo Anastacio, SP, Brazil. Children made a drawing expressing their vision about dental surgeon and the dental environment. The collected drawings were interpreted by a psychologist and grouped in Microsoft Office Excel spreadsheet and performed a statistical analysis using Fisher's exact test, logistic regression and regression simple logistics. Through this study it was possible to observe that 57,6% children analyzed in clinic of pediatric dentistry of Unoeste presented pleasant vision results of dental care, while 42,4% showed a hostile result, these being, mostly female children gender. In school, only 24,5% children presented pleasant result and 75,5% showed hostile result, the absence of gender difference. It is concluded that there was a statistically significant difference among the groups, and female gender children showed up more aversive.